Evaluasi Pembelajaran Daring Di Masa Pandemi Covid-19 Di Universitas Anwar Medika - Suwito Suwito; Abd. Syakur (Journal on Education, 2023)
This research on distance learning aims to show how to evaluate the implementation of online learning activities in universities that are faced during the covid-19 pandemic. Research on distance learning is part of a qualitative descriptive study with a survey method conducted online. Primary data collection was carried out by distributing online questionnaires to 30 respondents for lecturers who experienced the impact of the pandemic during the covid-19 period. In addition, the supporting data is secondary data from the results of the document filling out the google link. There are how many articles related to online learning during covid 19. The results of this study are from online learning, namely independent learning which seems forced to make students feel bored quickly and slow in online learning. Maximum practice is needed in independent study or group assignments so that students can be disciplined in learning. The weakness in online learning is the lack of communication between lecturers and students due to the encounter with the Zoom application with online learning.